Rapid Genetic Diagnosis of Citrin Deficiency by Multicolor Melting Curve Analysis - Zeng, Qinlong; Yang, Yingsong; Luo, Jiahong; Xu, Jinmei; Deng, Choufen; Yang, Yuanjuan; Tan, Shuming; Sun, Shuxiang; Li, Yuping; Ou, Tong (Frontiers in Pediatrics, 2021)
Citrin deficiency caused by SLC25A13 genetic mutations is an autosomal recessive disease, and four prevalent mutations including c.851_854del, c.1638_1660dup, IVS6+5G>A, and IVS16ins3kb make up >80% of total pathogenic mutations within the Chinese population. However, suitable assays for detection of these mutations have not yet been developed for use in routine clinical practice. In the current study, a real-time PCR-based multicolor melting curve analysis (MMCA) was developed to detect the four prevalent mutations in one closed-tube reaction. The analytical and clinical performances were evaluated using artificial templates and clinical samples. All four mutations in the test samples were accurately genotyped via their labeling fluorophores and Tm values, and the standard deviations of Tm values were indicated to be <0.2°C. The limit of detection was estimated to be 500 diploid human genomes per reaction. The MMCA assay of 5,332 healthy newborns from southern China identified a total of 107 SLC25A13-mutation carriers, indicating a carrier rate of 2%. The genotypes of 107 carriers and 112 random non-carriers were validated using direct sequencing and Long-range PCR with 100% concordance. In conclusion, the assay developed in this study may potentially serve as a rapid genetic diagnostic tool for citrin deficiency.